Gut microbiota of two invasive fishes respond differently to temperature - Zhang, Lixia; Yang, Zi; Yang, Fan; Wang, Gege; Zeng, Ming; Zhang, Zhongxin; Yang, Mengxiao; Wang, Zhanqi; Li, Zhibing (Frontiers in Microbiology, 2023)
Temperature variation structures the composition and diversity of gut microbiomes in ectothermic animals, key regulators of host physiology, with potential benefit to host or lead to converse results (ie. negative). So, the significance of either effect may largely depend on the length of time exposed to extreme temperatures and how rapidly the gut microbiota can be altered by change in temperature. However, the temporal effects of temperature on gut microbiota have rarely been clarified. To understand this issue, we exposed two juvenile fishes (Cyprinus carpio and Micropterus salmoides), which both ranked among the 100 worst invasive alien species in the world, to increased environmental temperature and sampled of the gut microbiota at multiple time points after exposure so as to determine when differences in these communities become detectable. Further, how temperature affects the composition and function of microbiota was examined by comparing predicted metagenomic profiles of gut microbiota between treatment groups at the final time point of the experiment. The gut microbiota of C.carpio was more plastic than those of M. salmoides. Specifically, communities of C.carpio were greatly altered by increased temperature within one week, while communities of M. salmoides exhibit no significant changes. Further, we identified 10 predicted bacterial functional pathways in C.carpio that were temperature-dependent, while none functional pathways in M. salmoides was found to be temperature-dependent. Thus, the gut microbiota of C. carpio was more sensitive to temperature changes and their functional pathways were significantly changed after temperature treatment. These results showed the gut microbiota of the two invasive fishes differ in response to temperature change, which may indicate that they differ in colonization modes. Broadly, we have confirmed that the increased short-term fluctuations in temperatures are always expected to alter the gut microbiota of ectothermic vertebrates when facing global climate change.